Pengaruh Kepemimpinan kharismatik terhadap Kompetensi Profesiobal Dosen Dalam Menghadapi Era Industrialisasi 4.0 - Saep Saepudin; Yanti Hasbian Setiawati; Nurul Hamidah (Jurnal Dirosah Islamiyah, 2019)
The purpose of this study was to determine and analyze the professional competence of Al-Ihya KuninganUniversity West Java lecturers; implementation of charismatic leadership at Al-Ihya Kuningan University, WestJava, and the influence of charismatic leadership on the professional competence of Al-Ihya Kuningan UniversityWest Java lecturers. The method used is a quantitative research model using simple regression and correlationanalysis. independent variables and one dependent variable that were examined in this study are: (1) charismaticleadership and (2) professional competence. Using saturated sample techniques and the population of lecturersat Al-Ihya Kuningan Islamic University, West Java, which amounted to 93 people. The results showed charismaticleadership had a direct positive effect on professional competence. The more positive charismatic leadership,professional competence tends to increase. The influence of charismatic leadership (X) on professionalcompetence (Y) is shown by the equation of a linear regression line that shows meaningful meaning. From theregression model it can be interpreted that changes in charismatic leadership scores will be followed by changesin scores on professional competence. The results indicate that charismatic leadership is one of the variables thatconstantly and stably contributes to professional competence. Efforts to improve professional competence canbegin with improving charismatic leadership first.